Sejarah Salahuddin Al-Ayyubi - Tamia, Fera; Indra (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2024)
The Ayyubid Dynasty, established by Salahuddin al-Ayyubi, played a significant role in Islamic history through complex socio-political transformations. Salahuddin faced substantial challenges in replacing the influence of the Fatimid Dynasty and Shia doctrine with Ahlusunnah Waljamaah as the official state doctrine. To achieve this goal, he implemented reforms in education, politics, and the military, including transforming Al-Azhar University into a Sunni educational center and establishing Sunni-based madrasas in Egypt. This study employs a qualitative approach with content analysis, examining books, journals, and historical documents to explore Salahuddin's leadership strategies. The findings reveal that Salahuddin successfully strengthened Ahlusunnah Waljamaah through the establishment of educational institutions, the appointment of Sunni scholars, and political and structural reforms that promoted socio-political stability. In the socio-cultural domain, he supported the formation of public institutions, such as hospitals, and encouraged cultural dialogue during the Crusades. This analysis underscores that Salahuddin's success was not limited to his military achievements but also included the socio-religious transformations that reinforced political stability and legitimacy. The study highlights the relevance of Salahuddin's strategies in building an inclusive and sustainable Islamic civilization, making his legacy a model for leadership focused on advancing civilization. These findings demonstrate the importance of synergy between religious vision and structural reforms in creating sustainable socio-political stability, offering significant contributions to contemporary Islamic leadership discourse.